Growth dependent changes in protein efficiency and amino acid composition in cultured meagre Argyrosomus regius - Baki, Birol; Öztürk, Dilara Kaya; Kerim, Murat (Journal of Fisheries, 2021)
The goal of this research was to determine the growth dependent changes in protein efficiency and amino acid composition of the cultured meagre Argyrosomus regius (Asso, 1801). The research was carried in net cages in a private company (Gokce Off-shore Sist.) in the Aegean Sea. Meagre of an initial weight of 8.22 ± 0.13 g reached to 373.96 ± 15.65 g in 420 days of production period. Average protein efficiency rate, protein store rate and protein consumption values of cultured meagre were 1.05 ± 0.11%, 11.49 ± 2.98% and 56.67 ± 14.52 g respectively. The total amino acid values varied between 14.97 ± 0.14 and 18.87 ± 0.10 g 100g–1, the statistical difference among the study periods was significant (p < 0.05). Most of the total essential (EAA), non-essential (NEAA), and branched‐chain amino acid values of cultured meagre were decreasing with increasing fish size but EAA/NEAA ratios were increasing. The findings of this study showed that the composition of amino acids and the consistency of meagre culture were adequate and appropriate for human consumption and nutrition.